2016
DOI: 10.1590/s1806-37562015000000221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulmonary function and respiratory symptoms in pyrochlore mine workers

Abstract: Objective: To identify respiratory symptoms and evaluate lung function in mine workers. Methods: This was a cross-sectional observational study involving production sector workers of a pyrochlore mining company. The subjects completed the British Medical Research Council questionnaire, which is designed to evaluate respiratory symptoms, occupational exposure factors, and smoking status. In addition, they underwent pulmonary function tests with a portable spirometer. Results: The study involved 147 workers (all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…Cigarette smoking imparts plummeting and perpetual hazards on the respiratory system, which in combination with dust-inhalation further casts resonating health perils on victims [38]; especially coal-mine workers [39]. Similar inferences were documented from Iran [40], Tanzania [41] and Ethiopia [42]; although researchers from Brazil defied such subtext [43]. Kuempel et al reported that emphysema was more severe amid coal miners than non-miners among ever and never smokers; while cumulative exposure to respirable coal-mine dust was a considerable predictor of emphysema severity once accounted for cigarette smoking, age at death, and race [44].…”
Section: Discussionmentioning
confidence: 88%
“…Cigarette smoking imparts plummeting and perpetual hazards on the respiratory system, which in combination with dust-inhalation further casts resonating health perils on victims [38]; especially coal-mine workers [39]. Similar inferences were documented from Iran [40], Tanzania [41] and Ethiopia [42]; although researchers from Brazil defied such subtext [43]. Kuempel et al reported that emphysema was more severe amid coal miners than non-miners among ever and never smokers; while cumulative exposure to respirable coal-mine dust was a considerable predictor of emphysema severity once accounted for cigarette smoking, age at death, and race [44].…”
Section: Discussionmentioning
confidence: 88%
“…Diabetes de tipo II 0 (0,0) 1 (0,1) 0 (0,0) 11 (1,4) 12 (1,5) Enfermedad cardiaca 1 (0,1) 0 (0,0) 0 (0,0) 1 (0,1) 2 (0,3) HIV 1 (0,1) 0 (0,0) 0 (0,0) 0 (0,0) 1 (0,1) En un principio, además de hacer un análisis descriptivo, se trató de correlacionar las variables en modelos bivariados en este estudio, con el fin de encontrar riesgos por medio de valores de la razón de momios (odds ratio, OR) pero dada la para la salud respiratoria con el paso del tiempo, según los resultados de la comparación entre grupos en cuanto a la sintomatología estudiada. Se acepta que las variables de esta encuesta pueden alterarse debido a múltiples factores, lo cual debe tenerse en cuenta en próximos estudios.…”
Section: Resultsunclassified
“…The evaluation through the HRQoL questionnaire is important to understand beyond the physical dimension but also the impact of biopsychosocial (Souza et al, 2021). Borges et al (2016), in their observational cross-sectional study, surveyed 147 workers at a mining company and obtained the following result: 22.44% of the workers had respiratory symptoms such as cough and dyspnea, while 17.69% of them showed changes in spirometric data.…”
Section: Borges Et Al (2016)mentioning
confidence: 99%